2014
DOI: 10.1088/0026-1394/51/3/354
|View full text |Cite
|
Sign up to set email alerts
|

Neutron activation analysis of the30Si content of highly enriched28Si: proof of concept and estimation of the achievable uncertainty

Abstract: Abstract:We investigated the use of neutron activation to estimate the 30 Si mole fraction of the ultra-pure silicon material highly enriched in 28 Si for the measurement of the Avogadro constant. Specifically, we developed a relative method based on Instrumental Neutron Activation Analysis and using a natural-Si sample as a standard. To evaluate the achievable uncertainty, we irradiated a 6 g sample of a natural-Si material and modeled experimentally the signal that would be produced by a sample of the 28 Si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…INRIM proposed to measure the amount-of-substance fraction of 30 Si by neutron activation [23]. A sample of the AVO28 crystal was analyzed using the TRIGA Mark II reactor.…”
Section: Molar Massmentioning
confidence: 99%
“…INRIM proposed to measure the amount-of-substance fraction of 30 Si by neutron activation [23]. A sample of the AVO28 crystal was analyzed using the TRIGA Mark II reactor.…”
Section: Molar Massmentioning
confidence: 99%
“…The application of INAA for the determination of the 30 Si mole fraction is feasible by counting the 1266.1 keV γ-photons emitted during the radioactive decay of 31 Si produced by activation of 30 Si via neutron capture reaction 30 Si­( n ,γ) 31 Si. The proof of concept and estimation of the achievable uncertainty in case of pure silicon materials highly enriched in 28 Si were reported …”
Section: Determination Of the 30si Mole Fractionmentioning
confidence: 99%
“…The measurement protocol and the derivation of the measurement equation, in the case of co-irradiation of the unknown and standard samples, have been described elsewhere. 4 The experiment was based on the simultaneous irradiation of the 28 Si-enriched unknown sample and a natural Si standard sample of known isotopic composition, followed by counting the 1266.1 keV γ-photons emitted by the 31 Si radioisotope produced from the 30 Si isotope via neutron capture reaction. Preliminary experimental results anticipated that the contribution to the uncertainty due to the knowledge of the natural isotopic composition of the standard was negligible.…”
mentioning
confidence: 99%
“…3 It was demonstrated that the application of Instrumental Neutron Activation Analysis (INAA) can add useful information to the isotopic composition of highly enriched 28 Si material. 4 A measurement protocol based on the INAA comparator method was applied to determine the x( 30 Si) of the AVO28; the resulting value, 1.043(19) × 10 −6 mol mol −1 , was obtained by irradiating a 5 g mass sample at the central channel, CC, of the Triga Mark II reactor of the University of Pavia. 5 Here and hereafter the standard uncertainty (k = 1) in parentheses applies to the last respective digits.…”
mentioning
confidence: 99%